Agronomic Evaluation and Yield Performance of Selected Barley (Hordeum vulgare L.) Landraces from Jordan - R. Al-Sayaydeh (International Journal of Agronomy, 2019)
Barley (Hordeum vulgare L.) landraces collected previously from main production areas across Jordan are expected to perform well under stressful environments. In this study, the agronomic performance of 10 Jordanian barley landraces and three local cultivars was evaluated in two locations for two growing seasons. Clear significant variations for all studied traits were observed among the selected genotypes, environments, and their interactions. The local cultivar Rum and Baladi landrace showed the best yield performance, while Herawi and Nabawi landraces produced the lowest yield across all environments. Clustering analysis using genotypic data from the iSelect 9k SNP barley array showed a clear grouping based on row type with 100% similarity level between the Syfi and Arabi landraces. The characterized Jordanian landraces can be used to improve barley resilience against climate change and associated conditions and are recommended in breeding programs to improve productivity under dry conditions.